Histórias do brincar: um estudo com adultos e suas trajetórias - Sartori, Gabriela Dias (Universidade Federal de São Carlos, 2021)
In the midst of a meritocratic, capitalist, productivist scenario, we bring the discussion and reflection about playing as an intrinsic experience of the human being. The objective of this research was to understand how a play experience is significant for adults in their life trajectories. The participants were 24 adults, 12 from Brazil and 12 from Spain, linked to different educational contexts (formal, non-formal and informal), whether through teaching, research, projects, groups of friends who get together for some kind of activity related to playing, interface with the areas of leisure, school education and art. The research question that moved this work was: What is the meaning of playing in adults' lives and how does this reflect on their life and professional experience? This study has a qualitative methodological approach and data collection was carried out through interviews. The theoretical framework dialogues with data analysis, addressing the formation of society, human beings and learning intertwined with playing, in the midst of their life trajectories. Data analysis occurred according to content analysis, respecting the subjects that emerged from the participants, dialogically approached with contributions from authors within such themes. In the narratives transformed into monads, we find playing adults, who conceptualized playing as it exists and manifests itself, in a timeless manner and as an experience of learning generated and re-visited throughout life. The monads addressed the themes: time, work, ludic elements, family, freedom, permanent learning, reflections on fun, encounters and bonds, conceptualizing the play, toys, and the record of what these adults play. The findings of playing as a form of bonds, relationships with oneself, with the other and with the world in a permanent way are significant. Thus, this research intended to contribute to the area of Education by proposing discussions on the importance of playing as a perennial and formative activity in human experience.

En medio de un escenario meritocrático, capitalista, productivista, traemos la discusión y reflexión sobre el juego como una experiencia intrínseca del ser humano. El objetivo de esta investigación fue comprender cómo la experiencia de juego es representada por los adultos en sus trayectorias de vida. Los participantes fueron 24 adultos, 12 de Brasil y 12 de España, vinculados a diferentes contextos educativos (formal, no formal e informal) sea a través de la docencia, la investigación, los proyectos, los grupos de amigos que se juntan para alguna actividad común relacionada con el juego, en una interfaz con las áreas de ocio, educación escolar y arte. La pregunta de investigación que movió este trabajo fue: ¿Cuál es el significado del juego en la vida de los adultos y cómo se refleja esto en su vida y experiencia profesional? Este estudio siguió un enfoque metodológico cualitativo y la recolección de datos se realizó a través de entrevistas. El marco teórico dialoga con el análisis de datos, abordando la formación de la sociedad, el ser humano y el aprendizaje entrelazados con el juego, en medio de sus trayectorias. El análisis de datos ocurrió de acuerdo al análisis de contenido, respetando los temas que surgieron de los participantes, trenzados dialógicamente con aportes de los autores dentro de dichos temas. En las narrativas transformadas en mónadas, encontramos adultos que juegan, que conceptualizan el juego tal como existe y se manifiesta, de manera atemporal y como una experiencia de aprendizaje generada y re-visitada a lo largo de la vida. Las mónadas abordaron los temas: tiempo, trabajo, elementos lúdicos, familia, libertad, aprendizaje permanente, reflexiones sobre la diversión, encuentros y vínculos, conceptos sobre el juego, juguetes y el registro de lo que juegan estos adultos. Son significativas las notas del juego como forma de vínculo, de relación con uno mismo, con el otro y con el mundo de forma permanente. Así, esta investigación pretende contribuir al área de la Educación proponiendo discusiones sobre la importancia del juego como actividad perenne y formativa en la experiencia humana.

Nel bel mezzo di uno scenario meritocratico, capitalista, produttivista, portiamo la discussione e la riflessione sul gioco come esperienza intrinseca dell'essere umano. L'obiettivo di questa ricerca era capire come l'esperienza di gioco è significata dagli adulti nelle loro traiettorie di vita. I partecipanti erano 24 adulti, 12 brasiliani e 12 spagnoli, legati a vari contesti educativi (formali, non formali e informali) sia attraverso l'insegnamento, la ricerca, i progetti, i gruppi di amici che si riuniscono per alcune attività comuni legate al gioco, in interfaccia con i settori del tempo libero, dell'istruzione scolastica e dell'arte. La domanda di ricerca che ha mosso questo lavoro è stata: qual è il significato del gioco nella vita degli adulti e come si riflette sulla loro vita e sulla loro esperienza professionale? Questo studio ha seguito un approccio metodologico qualitativo e la raccolta dei dati è stata effettuata attraverso interviste. Il quadro teorico dialoga con l'analisi dei dati, affrontando la formazione della società, gli esseri umani e l'apprendimento intrecciati con il gioco, nel mezzo delle loro traiettorie. L'analisi dei dati è avvenuta secondo l'analisi dei contenuti, nel rispetto delle problematiche emerse dai partecipanti, intrecciate dialogicamente con i contributi degli autori all'interno di tali temi. Nelle narrazioni trasformate in monadi troviamo adulti che giocano, che concettualizzano il gioco come esiste e si manifesta, in maniera atemporale e come esperienza di apprendimento generata e rivisitata nel corso della vita. Le monadi hanno affrontato i temi: tempo, lavoro, elementi ludici, famiglia, libertà, apprendimento permanente, riflessioni sul divertimento, incontri e legami, concetti sul gioco, giocattoli e registrazione di ciò che questi adulti giocano. Significative sono le note del suonare come forma di legame, di relazione con se stessi, con l'altro e con il mondo in modo permanente. Pertanto, questa ricerca intendeva contribuire all'area dell'Educazione proponendo discussioni sull'importanza del gioco come attività perenne e formativa nell'esperienza umana.
Stories of play: a study with adults and their trajectories
Keywords: Brincar; Adulto; Experiência; Narrativas (auto)biográficas; Mônadas; Play; Adult; Experience; (Auto)biographical narratives; Monads; Jugar; Gioco; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO